Zein-based nano-delivery systems for encapsulation and protection of hydrophobic bioactives: A review - Yan, Xiaojia; Li, Moting; Xu, Xingfeng; Liu, Xuebo; Liu, Fuguo (Frontiers in Nutrition, 2022)
Zein is a kind of excellent carrier materials to construct nano-sized delivery systems for hydrophobic bioactives, owing to its unique interfacial behavior, such as self-assembly and packing into nanoparticles. In this article, the chemical basis and preparation methods of zein nanoparticles are firstly reviewed, including chemical crosslinking, emulsification/solvent evaporation, antisolvent, pH-driven method, etc., as well as the pros and cons of different preparation methods. Various strategies to improve their physicochemical properties are then summarized. Lastly, the encapsulation and protection effects of zein-based nano-sized delivery systems (e.g., nanoparticles, nanofibers, nanomicelles and nanogels) are discussed, using curcumin as a model bioactive ingredient. This review will provide guidance for the in-depth development of hydrophobic bioactives formulations and improve the application value of zein in the food industry.